2007
DOI: 10.1016/j.advwatres.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The groundwater–land-surface–atmosphere connection: Soil moisture effects on the atmospheric boundary layer in fully-coupled simulations

Abstract: This study combines a variably-saturated groundwater flow model and a mesoscale atmospheric model to examine the effects of soil moisture heterogeneity on atmospheric boundary layer processes. This parallel, integrated model can represent spatial variations in land-surface forcing driven by three-dimensional (3D) atmospheric and subsurface components. The development of atmospheric flow is studied in a series of idealized test cases with different initial soil moisture distributions generated by an offline spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
219
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 246 publications
(237 citation statements)
references
References 53 publications
6
219
0
Order By: Relevance
“…As noted above the raison d'être of land models is to provide the lower boundary condition for the atmosphere, so the interest here is the extent to which the different model implementations of groundwater affect soil moisture dynamics and land-atmosphere fluxes [Maxwell et al, 2007;Maxwell and Kollet, 2008b]. Interestingly, with the notable exception of the Catchment model , none of the TOPMO-DEL implementations represent the impact of subgrid variability in water table depth on soil moisture dynamics.…”
Section: 1002/2015wr017096mentioning
confidence: 99%
“…As noted above the raison d'être of land models is to provide the lower boundary condition for the atmosphere, so the interest here is the extent to which the different model implementations of groundwater affect soil moisture dynamics and land-atmosphere fluxes [Maxwell et al, 2007;Maxwell and Kollet, 2008b]. Interestingly, with the notable exception of the Catchment model , none of the TOPMO-DEL implementations represent the impact of subgrid variability in water table depth on soil moisture dynamics.…”
Section: 1002/2015wr017096mentioning
confidence: 99%
“…Liang et al 2003;Yeh and Eltahir 2005;Stöckli et al 2008) and through coupling with an explicit ground water model (e.g. York et al 2005, Maxwell andMiller 2005;Maxwell et al 2007). …”
Section: Temperaturementioning
confidence: 99%
“…It is argued that the coupled modeling approach has the advantage of including the soil moisture redistribution feedback in the lower boundary conditions of atmospheric models, which may lead to an improved representation of water and energy fluxes between land and atmosphere (Maxwell et al 2011;Shrestha et al 2014;Senatore et al 2015;Arnault et al 2016;Wagner et al 2016). Maxwell et al (2007) showed that the fully coupled modeling system yields a topographically driven soil moisture distribution and depicts a spatial and temporal correlations between surface and lower atmospheric variables and water depth. This may suggest that the fully coupled models are regulated by the geographical location of the area under study.…”
Section: Introductionmentioning
confidence: 99%